Occurrence of dark septate endophyte fungi in Oryza glumaepatula roots in Amazonia - Pereira, Gilmara Maria Duarte; Ribeiro, Karen Gonçalves; Fernandes Júnior, Paulo Ivan; Vital, Marcos José Salgado; Kasuya, Maria Catarina Megumi; Zilli, Jerri Édson (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to assess the occurrence of dark septate endophyte fungi (DSEF) in Oryza glumaepatula in Amazonia, and its in vitro colonization capacity. Oryza glumaepatula plants were collected in forest and cerrado areas of the Roraima state, Brazil. The roots were prepared to observe septate melanized hyphas and microesclerotia. The isolation of fungi was done in agar malte medium. Dark septate endophyte fungi were observed in plants from both environments, with higher colonization on those collected in the forest. One isolate was able to colonize the original host and also Oryza sativa plants, exhibiting typical DSEF structures in rice healthy plants.